Adherence to early mobilisation: Key for successful enhanced recovery after liver resection. Issue 10 (October 2016) - Yip, V.S.; Dunne, D.F.J.; Samuels, S.; Tan, C.Y.; Lacasia, C.; Tang, J.; Burston, C.; Malik, H.Z.; Poston, G.J.; Fenwick, S.W.
Abstract: Background: Enhanced Recovery After Surgery (ERAS) has been proven effective in liver surgery. Adherence to the ERAS pathway is variable. This study seeks to evaluate adherence to key components of an ERAS protocol in liver resection, and identify the components associated with successful clinical outcomes. Method: All patients undergoing liver resections for two consecutive years were included in our ERAS pathway. Six key components of ERAS included preoperative assessment, nutrition and gastrointestinal function, postoperative analgesia, mobilisation and discharges. Successful accomplishment of ERAS was defined as hospital discharge by postop day (POD) 6. Adherences of these elements were compared between the successful and un-successful groups. Results: During the studied period, 223 patients underwent liver resections, among which 103 had major hepatectomies. N = 147 patients (66%) were discharged within our ERAS protocol target (6 days). On multivariable analysis, sitting out of bed by POD 1 (p < 0.03), walking by POD 3 (p = 0.03), removal of urinary catheter by POD 3 (p < 0.01), and avoiding major complications (p < 0.01) were factors associated with successful completion to our ERAS protocol; whereas advanced age (p = 0.34) and discontinuation of PCA/epidural by POD 3 (p = 0.50) were not significant parameters. There was a significant difference in the length of stay (p < 0.01) following major and minor liver resection, of which the indications for surgery also varied significantly. There was no difference in hospital re-admission rate, and morbidity and mortality between major and minor liver resection. Conclusions: Facilitating early mobilisation and reducing postoperative complications are keys to successful outcomes of ERAS in liver resection.